Incidence and factors associated with anemia among Thais aged 6-12 months at Pakchong Nana Hospital - Chanprakaisi, Warasin (Maharat Nakhon Ratchasima Hospital Journal, 2024)
Introduction: Anemia among Thais aged 6-12 months is one of major public health problem of Thailand. The major cause of anemia in most children is iron deficiency resulting in slow growth, fatigue, inactivity, attention deficit, and learning problem. In addition, anemia is a major cause of cognitive dysfunction. Patients and Method: The aim of this prospective study was to find the incidence of anemia, the risk opportunity, and predicting factors contributing to anemia among Thais aged 6-12 months. Data were collected using the interview care-givers of children who accepted vaccination at child health supervision clinic of Pakchong Nana Hospital during 1 July-31 October 2018. All 194 children firstly had their blood checked for anemia. Data were presented using the descriptive statistics and analyzed using correlation and regression analysis. Results: Of 194 children, 35 were anemic (18.0 %) whose hematocrit was less than 33 %, averaged Hct of 25.5%. The ratio of male to female children with was 77.1:22.9. From analysis of risk opportunity of anemia, children who had been breastfed more than six months had 8.2 times of opportunity for anemia as compared with children who had been breastfed less than six months (95 % C.I. 3.6-18.7). Pregnant women with anemia had opportunity for having anemic children 7.6 times of women without anemia (95% C.I. 2.4-23.5). With multiple regression analysis, pregnant women with earning less than 10,000 Baht, Hct of pregnant women < 33%, gestational age < 37 weeks, breast feeding > 6 months, Hct of neonates < 45% were significant factors for prediction of anemia (p 0.01). Conclusion: From incidence and factors associated with anemia, the best prevention methods of anemia were: do not leave the pregnant women to lack of iron, to extend breast feeding till 6 months, to start food supplement at 4-6 months of age, and to add oral liquid iron at 4 months of age for full term but since birth for preterm. The blood check for anemia should cover widely for early detection of anemia.